Pengaruh Macam Formula Poc Bioflok Terhadap Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.) dan Selada (Lactuca sativa L.) dalam Polybag - Ikhsan Arjin; Sunaryo, Yacobus; Darnawi (JURNAL ILMIAH AGROUST, 2022)
The aim of this study is to know the effect and interaction formulation of bioflok POC administration to growth and result of mustard and lettuce in polybag. Research has been carried out at the Green House. Faculty of Agriculture, University of Sarjanawiyata Tamansiswa Yogyakarta. This study was conducted in January – April 2022. Altitude of 100 meters above sea level, with average temperature of 25.6°C. This research was conducted using a 4 x 2 factorial experiment with Completely Randomized Design (CRD), with 2 treatment factors and 3 replications. The first factor is the formulation of POC F0, F1, F2 and F3. F0 means without POC, F1 is mixture of bioflok catfish waste and coconut water, F2 is mixture of bioflok catfish waste, coconut water and EM4 and F3 is mixture of bioflok catfish waste, coconut water, EM4 and molasses. The second factor is types of plants, that is mustard (M1) and lettuce (M2). Analisis of observational variable data used variance analysis level of 5% and followed by Duncans Multiple Range Test (DMRT) level of α = 5%. The result of the experiment indicated that there was no interaction between the formulation of bioflok POC application on all observed variables to growth and result of mustard and lettuce in polybag. Mustard has the same result (fresh weight per clump) as lettuce. Mustard has the higher growth (dry weight per clump) than lettuce. The mixture of bioflok catfish waste and coconut water POC produced higher result than the other formulation. F1, F2 and F3 have the same growth, but formulation 1 has higher growth than F0 (without POC).